Análisis del impuesto a la salida de divisas y su impacto en la recaudación tributaria nacional en el periodo 2020 - 2021.. - Chiliquinga Tutasig, Paola Alexandra (2023)
The Foreign Exchange Outflow Tax is a fiscal measure that seeks to tax international transactions that leave the country, i.e. it helps to control capital flight and generate tax revenues. The objective of this research is to determine the impact of the tax on foreign exchange outflows on the national tax collection in the period 2020 - 2021. The methodology adopted in this study is based on a quantitative approach, descriptive and correlational research, and numerical and statistical analysis of data obtained by the Internal Revenue Service (IRS). These data come from the tax collection specific to the ISD tax of the 24 provinces of the country, where the variations and collection levels of the different economic activities are evidenced. The results obtained from the research allow identification that Pichincha and Guayas present a relative variation of 23.92% and 33.06% because they are considered economic, financial, and industrial centers of the country, while the rest of the provinces contribute 1%, this data is not relevant because, in reality, their contribution to the total budget is minimal. Thus concluded that the variable under study presented a deficit in the trade balance resulting from the fact that imports exceeded exports.